N, N′‐Dioxide–Lanthanum(III)‐Catalyzed Asymmetric Cyclopropanation of 2‐Cyano‐3‐arylacrylates with 2‐Bromomalonates. Issue 11 (6th April 2017) - Zhang, Yuheng; Lin, Lili; Chen, Yushuang; Liu, Xiaohua; Feng, Xiaoming
Abstract: An efficient N, N′ ‐dioxide–lanthanum(III) complex catalytic system has been developed for the diastereo‐ and enantioselective Michael‐initiated ring‐closure (MIRC) reaction of 2‐cyano‐3‐arylacrylates with 2‐bromomalonates. Various chiral cyclopropanes with multiple substitutions were obtained in high yields (up to 93%) with excellent dr (>95:5 dr ) and good ee values (up to 91% ee ). The catalytic system also worked for the tandem halogenation/asymmetric MIRC reaction of α, β‐unsaturated nitriles, malonates and NBS. Besides, a possible catalytic model has been proposed to explain the origin of the stereoselectivity. Abstract :